2020
DOI: 10.1038/s41598-020-63122-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Adaptation of Juvenile Pacific Abalone Haliotis discus hannai to Heat Stress

Abstract: Temperature fluctuation is a key abiotic factor for the growth and survival of Pacific abalone Haliotis discus hannai, particularly during climate change. However, the physiological mechanism underlying the abalones' response to heat stress remains unknown. We sought to understand the metabolic adaptation mechanism of Pacific abalone to heat stress for further analyzing its heat tolerance capacity. For two groups experienced different acclimate temperature (10 °C and 30 °C for 62 days), the Pacific abalone juv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…The fact that temperature has pervasive effects on biological structures and rates of physiological activity underlies the importance of elucidating the fundamental mechanistic determinants of thermal optima and thermal limits, which play crucial roles in determining species distribution patterns and sensitivities to anthropogenic climate change (Somero, 2012;Somero et al, 2017). Although much progress has been made in clarifying the bases of biochemical and physiological adaptation (Angilletta, 2009;Cossins and Bowler, 1987;Somero et al, 2017), particularly at the level of individual proteins (Dong et al, 2018;Liao et al, 2017;Somero, 2004), metabolic pathways (Noda-Garcia et al, 2018;Götze et al, 2020;Xu et al, 2020), and membrane structure and function (e.g. homeoviscous and homeophasic adaption; Hazel, 1995;Logue et al, 2000;Somero et al, 2017), there remain many unanswered questions about the mechanisms that set the thermal limits for life.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that temperature has pervasive effects on biological structures and rates of physiological activity underlies the importance of elucidating the fundamental mechanistic determinants of thermal optima and thermal limits, which play crucial roles in determining species distribution patterns and sensitivities to anthropogenic climate change (Somero, 2012;Somero et al, 2017). Although much progress has been made in clarifying the bases of biochemical and physiological adaptation (Angilletta, 2009;Cossins and Bowler, 1987;Somero et al, 2017), particularly at the level of individual proteins (Dong et al, 2018;Liao et al, 2017;Somero, 2004), metabolic pathways (Noda-Garcia et al, 2018;Götze et al, 2020;Xu et al, 2020), and membrane structure and function (e.g. homeoviscous and homeophasic adaption; Hazel, 1995;Logue et al, 2000;Somero et al, 2017), there remain many unanswered questions about the mechanisms that set the thermal limits for life.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the transport of live aquatic animals deliberately delivered to distant farms in large quantities could have facilitated the transmission of bacteria among different regions or countries. For our cases, the epidemiological investigation showed that a large number of abalone, sea cucumber, and other aquatic animals were transported from Liaoning and Shandong to Fujian province from later October to early November, as high temperatures in South China would promote the growth of aquatic animals and shorten their life cycle ( 22 ). Such large-scale movement of live aquatic animals from north to south (or the reverse direction) would have profound effects on the mixing of V. parahaemolyticus populations.…”
Section: Discussionmentioning
confidence: 93%
“…Understanding how the environment influences the metabolism and growth of abalone in fished populations is central to effective fisheries management (Naylor et al, 2006 ). Metabolic studies have previously been performed on juvenile or adult H. midae (Venter et al, 2019 ), H. iris (Grandiosa et al, 2018 ), H. fulgens (Tripp-Valdez et al, 2019 ) and H. discus hannai (Xu et al, 2020 ), yet metabolomics characterisation of a population to guide stock and fisheries management or translocation practises remains an untouched subject.
Fig.
…”
Section: Resultsmentioning
confidence: 99%